Characterization of Morinda tomentosa genotypes under rainfed conditions of western India - SINGH, A K; SINGH, SANJAY; JOSHI, H K; MAKWANA, PURNIMA (The Indian Journal of Agricultural Sciences, 2014)
A field trial was conducted to characterize Morinda tomentosa Heyne ex Roth genotypes which were established during 2009 under field condition during the years 2011-13 at Experimental Farm of Central Horticultural Experiment Station (CIAH-ICAR) Vejalpur, Panchmahals (Godhra), Gujarat. The vegetative morphomatrix in terms of plant height, stem girth, plant spread, number of primary branches and number of secondary branches varied between 3.10-4.70 cm, 19.10-36.08 cm, 2.27-3.87 m, 6.23-13.45 and 12.12-26.00, respectively, whereas leaves morphology, viz. leaf length, breadth, petiole length and vein pairs ranged between 15.00-25.00 cm, 8.00-16.50 cm,1.25-2.29 cm and 7.43-11.33 per leaf, respectively. Yield /plant during 3rd year varied between 3.50-9.41 kg being highest in CHESN 1 and the lowest in CHESN 21 in all the evaluated genotypes. The quantitative fruit characters in terms of fruit weight, length, breadth, number of pyrines, number of seed/fruit and fresh weight of seed ranged between 19.20-47.10 g, 2.49-4.80 cm, 2.34-3.98 cm, 10.95-23.95, 25.17-50.65 and 0.06-0.11 g, respectively. Variations in values of TSS, pH, vitamin C and acidity, protein, phenols, tannins, Ca, K, Na, and Zn ranged between 6-120 brix, 3.50-7.00, 21.15-40.15 mg/ 100g, 1.16-1.51 per cent, 0.09-0.29 g, 11.12-20.05 mg, 0.25-0.46 g, 90.10-102.00 mg, 36.12-49.92 mg, 80.16-93.90 mg and 0.10-0.29 mg among the genotypes characterized for their biochemical composition. Based on the overall observations, CHESN 1, CHESN 16 and CHESN 31 were found to better with respect to most of the qualitative and quantitative characters than rest of the genotypes evaluated under rainfed conditions of western India.